Population Shift of The Family Scaridae: An Ecological Study in The Threatened Habitat of Tikus Island - Novita Nanda Syafitri; Deddy Bakhtiar; Ari Anggoro; Maestro Munru; Herni Iman Sari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Parrotfish have an essential role in maintaining the balance and health of coastal and marine ecosystems, but the existence of coral reefs on Pulau Tikus as their habitat has been degraded, threatening the survival of these fish. This study aims to determine the abundance of fish in the Scaridae family based on coral reef cover and the relationship with coral reef cover. Sampling was conducted in February-May 2021 in the waters of Pulau Tikus Bengkulu. Reef fish observations used UVC (Underwater Visual Census), while coral reef cover used the LIT (Line Intercept Transect) method. The highest reef fish abundance was at station 1 at 0.06 ind/m2, while the lowest was at station 3 at 0.02 ind/m2. The highest percentage of coral cover was at station 1 at 70.44% and the weakest at station 3 at 8.18%. The relationship between the percentage of coral cover and parrotfish abundance strongly correlates with a value of R = 0.62.